Student Anxiety and Math Learning Outcomes in Grade 4 During Covid-19: Hubungan Kecemasan Siswa dengan Hasil Pembelajaran Matematika pada Siswa Sekolah Dasar Kelas 4 Selama Pandemi Covid-19 - Lutfi Dwi Lestari; Kemil Wachidah (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aimed to examine the relationship between student anxiety and mathematics learning outcomes among fourth-grade students at SDN Sugihwaras Candi during the Covid-19 pandemic. The research employed a survey method with a saturated sampling technique, resulting in a sample size of 60 fourth-grade students. Hypothesis testing was conducted using a correlation test, and the results revealed a significant negative relationship (-0.718) between student anxiety and mathematics learning outcomes. The findings indicate a strong association between higher levels of anxiety and lower achievement in mathematics among fourth-grade students during the Covid-19 pandemic. These results emphasize the need for interventions and support to address student anxiety, as it can significantly impact their academic performance in mathematics. Highlights: Student anxiety: Examining the impact of anxiety on students' academic performance in mathematics. Mathematics learning outcomes: Investigating the relationship between anxiety levels and achievement in math. Fourth grade students: Assessing the effects of anxiety on fourth graders' learning during the Covid-19 pandemic. Keywords: student anxiety, mathematics learning outcomes, fourth grade, Covid-19 pandemic, quantitative approach